2018
DOI: 10.15282/mohe.v7i2.186
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline problem: Factors influencing the underrepresentation of women in top leadership positions in sports organisation

Abstract: National Sports Associations, National and International Sports Federations and even International Olympic Committee continue to struggle meeting the 20% representation quota of women in executive boards. Although women’s representation as athletes, coaches and officials increased in national and international sports competitions but not in leadership particularly in top positions. In sports leadership, empirical research showed statistical figures that women have gained access in leadership pipeline however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Mentors help prepare colleagues for leadership roles by providing insights and guiding development while sponsors go a step further by advocating, positioning, and risking their reputation for qualified candidates (Ibarra et al, 2010 ). Aman et al ( 2018 , p. 152–153) noted that “through social networking and mentoring women role models in sport administration lend their voices to women, show women in decision-making positions, and realistically portray the possibility that women are qualified to be sport leaders.” Women need to see other women in these life roles, and envision themselves occupying a similar role in the future. Role models help build confidence in others to do the same (Gardner and Laskin, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mentors help prepare colleagues for leadership roles by providing insights and guiding development while sponsors go a step further by advocating, positioning, and risking their reputation for qualified candidates (Ibarra et al, 2010 ). Aman et al ( 2018 , p. 152–153) noted that “through social networking and mentoring women role models in sport administration lend their voices to women, show women in decision-making positions, and realistically portray the possibility that women are qualified to be sport leaders.” Women need to see other women in these life roles, and envision themselves occupying a similar role in the future. Role models help build confidence in others to do the same (Gardner and Laskin, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aman et al ( 2018 , p. 154) suggested that “… while self-promoting behaviors are rare in women, men use self-promoting behaviors to access leadership positions and gain economic rewards,” so women must do the same (Sandhu and Mehta, 2008 ). In the male-dominated sport's environment, women often encounter prejudices that impact the perceptions of their effectiveness (Eagly and Karau, 2002 ; Eagly and Carli, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women often underestimate their contributions and abilities, they often think that they lack the skills and ability to position and promote themselves relative to their men counterparts. As a result, women frequently leave middle management roles early due to a perceived lack of support, recognition, and respect (Burton & Leberman, 2017;Aman et al, 2018). This is also described by other researchers (Aman et al, 2018;Hancock & Hums, 2006;Helfat et al, 2006;Pell, 1996;Ragins et al, 1998;White, 2004) as the "leaky pipeline".…”
Section: Self-inflicted Barriers and Perceptionsmentioning
confidence: 93%
“…As a result, women frequently leave middle management roles early due to a perceived lack of support, recognition, and respect (Burton & Leberman, 2017;Aman et al, 2018). This is also described by other researchers (Aman et al, 2018;Hancock & Hums, 2006;Helfat et al, 2006;Pell, 1996;Ragins et al, 1998;White, 2004) as the "leaky pipeline". Kay & Shipman (2014) have proven that men will apply for jobs when they meet a minimal percent of the requirements, whereas women will only apply to the job when they meet all of the requirements.…”
Section: Self-inflicted Barriers and Perceptionsmentioning
confidence: 93%